An Exploratory Investigation of Parental Incarceration, Emotional Independence, and Adult Children’s Criminal Activity - Finkeldey, Jessica (Journal of developmental and life-course criminology, 2021)
Although research suggests that parental incarceration is associated with intergenerational continuity in crime, the mechanisms underlying this association remain unclear. Using multi-population structural equation modeling and data from the Toledo Adolescent Relationships Study (n = 1207), the current study explored specific experiences associated with labeling as well as internalizing labels, including experiencing corporal punishment during childhood, criminal arrests during adolescence, and identifying as a troublemaker/partier in young adulthood (measured with reflected appraisals), as potential mechanisms linking parental incarceration and young adults’ offending. We assessed whether this association differed by young adults’ level of emotional independence, that is, freedom from the need for parental approval. We found that parental incarceration indirectly influenced criminal activity particularly through identifying as a troublemaker/partier during young adulthood but only for those who sought parental approval. Overall, we concluded that high emotional independence, or not seeking parental approval, may be a protective factor that facilitates intergenerational discontinuities in crime.